Correlation between the quality of calcaneal fracture reduction and time to return to work - Motizuki, Fabielle Patrícia Zanardini; Martynetz, Juliano Rodrigo; Polati, Mário Fábio; Paula, Sidney Silva de; Klein Júnior, Afonso; Suzuki, Gustavo Yuiti Kaneko (Scientific Journal of the Foot & Ankle, 2018)
Objective: The aim of this study is to test the hypothesis that patients with calcaneal fractures who are surgically treated and have Böhler and Gissane angles restored to normal have a faster return to work than patients without restoration of these angles. Calcaneal fractures represent 1-2% of all fractures, and approximately 75% of these are articular, indicating surgical treatment. Joint involvement results in functional limitation and can lead to late complications such as chronic pain, subtalar arthrosis, difficulty walking, and deformities. Methods: Lateral radiographs of the calcaneus of 44 patients who underwent surgical treatment for calcaneal fracture during the period from 2014 to 2016 were analysed to measure the Böhler and Gissane angles and to evaluate the association of their restoration to normal with the time to return to work. Results: Among the patients, 70.2% presented restoration of the Böhler angle and 44.7% presented restoration of the Gissane angle with surgery. The mean time away from work was 8.38 months. A total of 76.6% of patients returned to the same function. Patients who had good fracture reduction had a shorter time to return to work, but this result was not statistically significant. Conclusion: Surgical restoration of angles can positively influence the functional outcomes of patients, but this is not the only variable and thus should not be exclusively used to analyse the functional outcome and time to return to work of patients. Level of Evidence III; Therapeutic Studies; Cases Series.